Frequency upconversion in Er3+-doped fluoroindate glasses pumped at 1.48 μm - Maciel, G. S.; Araújo, Cid B. de; Messaddeq, Younes [UNESP]; Aegerter, M. A. (American Physical Society (APS), 1997)
We report on efficient frequency upconversion in Er3+-doped fluoroindate glass. The process is observed under 1.48 μm laser diode excitation and results in fluorescence generation in the range from ultraviolet to near-infrared radiation. The study was performed for samples containing 1, 2, and 3 ErF3 mol % in the range of temperatures from 24 to 448 K. The upconverted signals were studied as a function of the laser intensity, and their dynamical behavior is described using a rate equation model which allows us to obtain the energy transfer rates between Er3+ ions in pairs and triads.